Purification and Functional Characterization of a New Endoglucanase from Pleurotus djamor PLO13 Produced by Solid-State Fermentation of Agro-Industrial Waste - Monizy da Costa Silva; Ricardo Bezerra Costa; Marta Maria Oliveira dos Santos Gomes; Josiel Santos do Nascimento; Andreza Heloiza da Silva Gonçalves; Jéssica Alves Nunes; Marta Angelo dos Santos; Francis Soares Gomes; José Maria Rodrigues da Luz; Luciano Aparecido Meireles Grillo; Hugo Juarez Vieira Pereira (Fermentation)
The increasing generation of agro-industrial waste and its improper disposal have raised significant environmental concerns, highlighting the urgent need for sustainable alternatives which would repurpose these materials. In this context, enzymes such as endoglucanase play a critical role in degrading lignin–cellulose biomass by catalyzing the breakdown of β-1,4-glycosidic bonds in cellulose, thereby converting it into fermentable sugars with diverse industrial applications. This study aimed to investigate the production, purification, and characterization of an endoglucanase produced by the fungus Pleurotus djamor PLO13, using coconut fiber, sugarcane bagasse, wheat bran, and pineapple crown as substrates. Endoglucanase activity was measured by the Miller method (1959), using 2% (w/v) carboxymethyl cellulose (CMC) as substrate. Solid-state fermentation (SSF) was found to be highly efficient for enzyme synthesis, with wheat bran emerging as the most effective substrate, yielding an enzyme production of 7.19 U after 120 h of cultivation. The endoglucanase was purified through ethanol precipitation and ion-exchange chromatography using DEAE-Sepharose, achieving a recovery rate of 110%, possibly due to removal of inhibitors present in the crude extract. The purified enzyme exhibited stability across a broad pH range and thermostability, with optimal activity at pH 5.0 and 50 °C. Furthermore, the enzyme was activated by EDTA, Mn2+, and Ca2+, while being inhibited by Mg2+. Notably, the enzyme demonstrated halotolerance, with activity increasing by 60% upon the addition of 3 M NaCl. Kinetic analysis revealed that the purified enzyme showed affinity to the CMC substrate at the analyzed parameters (pH 5.0 and 50 °C), with Km and Vmax values of 0.0997 mg/mL and 112.2 µg/min/mL, respectively. These findings suggest that the endoglucanase from P. djamor PLO13 has promising potential for biotechnological applications, underscoring the feasibility of the use of lignocellulosic waste as sustainable substrates in industrial processes.